Implementation of Madrasah Principal Policy in Improving Teacher Performance at MA Raudlatul Ulum Sumberwringin - Andini Andini (Sustainable, 2024)
This research aims to find out what policies are implemented by school principals to improve teacher performance at MA Raudlatul Ulum Sumberwringin. The research method used is descriptive qualitative with a multicase study type of research. This research used a purposive sampling technique, namely interview, observation and documentation techniques. Using Miles Hubberman data analysis techniques, namely data collection, data reduction, data display and data verification. To present the data, the validity of the data is ensured by using data source triangulation and method triangulation. The results obtained from research on the implementation of school principal policies in improving teacher performance at MA Raudlatul Ulum Sumberwringin are: 1) providing training to each individual according to their field of expertise, 2) providing motivation, and 3) evaluating teacher performance. Implementation of madrasah principal policies can significantly improve teacher performance, which ultimately has a positive impact on the quality of education in Madrasahs. Factors that support the successful implementation of this policy include visionary leadership, effective communication between school principals and teachers, and support from various parties. Madrasah principals rely heavily on commitment, leadership skills and the ability to adapt to the specific needs and conditions of the school.